2021
DOI: 10.1371/journal.pntd.0009128
|View full text |Cite
|
Sign up to set email alerts
|

Effects of steroid therapy in patients with severe fever with Thrombocytopenia syndrome: A multicenter clinical cohort study

Abstract: Background Severe fever with thrombocytopenia syndrome (SFTS) is an acute, febrile, and potentially fatal tick-borne disease caused by the SFTS Phlebovirus. Here, we evaluated the effects of steroid therapy in Korean patients with SFTS. Methods A retrospective study was performed in a multicenter SFTS clinical cohort from 13 Korean university hospitals between 2013 and 2017. We performed survival analysis using propensity score matching of 142 patients with SFTS diagnosed by genetic or antibody tests. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 21 publications
(12 reference statements)
0
23
0
Order By: Relevance
“…Although the role of CS in severe acute respiratory syndrome coronavirus 2 infections remains controversial, a British clinical trial has reported the efficacy of CS for treating COVID-19 [ 24 ]. A study in South Korea found that the survival time in the CS-treated group was shorter than that in the non-CS-treated group in mild cases (Acute Physiology and Chronic Health Evaluation II score <14) [ 14 ]. There had been no report to verify the effectiveness of CS for SFTSV infection in combination with ribavirin or favipiravir.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the role of CS in severe acute respiratory syndrome coronavirus 2 infections remains controversial, a British clinical trial has reported the efficacy of CS for treating COVID-19 [ 24 ]. A study in South Korea found that the survival time in the CS-treated group was shorter than that in the non-CS-treated group in mild cases (Acute Physiology and Chronic Health Evaluation II score <14) [ 14 ]. There had been no report to verify the effectiveness of CS for SFTSV infection in combination with ribavirin or favipiravir.…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports have shown that corticosteroid (CS) administration was effective for patients with SFTS and hemophagocytic syndrome (HPS) [ 13 ]. However, a retrospective study conducted in South Korea found that the CS-treated group had a higher mortality rate than the non-CS-treated group [ 14 ]. Owing to some reports on secondary fungal infections after CS administration for several SFTS cases [ 15 ], the safety of CS in SFTS needs to be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with observations in humans. Indeed, a multivariate analysis by Jeong et al revealed that advanced age is a significant risk factor associated with high 30-day mortality in SFTS patients (adjusted hazard ratio (aHR), 1.10; 95% confidence interval (CI), 1.04–1.17) [ 79 ]. The occurrence of secondary infections in SFTS patients has also been reported and can be triggered by the presence of bacteria or fungi.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…However, considering these case reports, we assume that SFTS can be a risk factor for IPA, even in patients without any apparent risk factor for invasive aspergillosis. Jung et al evaluated the effects of steroid therapy in patients with SFTS [ 79 ] and reported a significant difference in mean 30-day survival between the steroid and nonsteroid groups of mild SFTS patients that was characterized by an APACHE II score of less than 14 points after propensity matching. Moreover, survival differences between the nonsteroid and the early and late steroid groups were statistically significant.…”
Section: Sfts Treatmentmentioning
confidence: 99%
“…At present, only some case reports showed the effectiveness of CS treatment in severe SFTS and patients with encephalopathy in the early stage of SFTSV infection (Nakamura et al, 2018),however, there were two retrospective cohort studies abroad suggested the possible negative effects of CS therapy in mortality and secondary infection in patients with SFTS (Jung et al,2021;Kawaguchi et al,2021). Therefore, The efficacy and safety of CS therapy for SFTS patients still need to be better evaluated.This article aims to retrospectively analyze the efficacy and safety of short-term low-to-moderate dose CS therapy in acute patients with SFTS.…”
Section: Introductionmentioning
confidence: 99%